Final answer:
To solve the equation 6(x - 1) = 4(x - 2), expand both sides, then rearrange and simplify to isolate x, resulting in the solution x = -1.
Step-by-step explanation:
To solve the equation 6(x - 1) = 4(x - 2), we first expand both sides:
6x - 6 = 4x - 8.
Next, we rearrange the terms to isolate the variable x:
6x - 4x = -8 + 6.
This simplifies to:
2x = -2.
Dividing both sides by 2 gives us the solution:
x = -1.
The answer is in its simplest form, so it is already reduced, and being a whole number, it doesn't need to be expressed as a mixed number.